Implementation of the Consumer Protection Law in Business Development in Indonesian Society - Hasdiana Juwita Bintang; Lidya Rahmadani Hsb; Pema Suryanta Bintang (Yayasan Multidimensi Kreatif, 2025)
This study aims to describe the implementation of the Consumer Protection Law in Business Development in Indonesia. The research method used is descriptive with a normative research type, the data collection method is done by literature study, the analysis used is qualitative analysis. A brief overview in the study is This dynamic reflects how existing policies attempt to create a balance of interests, but there are still challenges in their implementation. The inability of current regulations to fully protect consumers from detrimental business practices raises questions about their effectiveness. Thus, steps are needed to strengthen the consumer protection system, including stricter law enforcement and increased awareness among business actors, in order to create fair and sustainable business practices.